To find the solution for the system of equations given in the table, we need to identify the x-value where the two equations \( y = x + 6 \) and \( y = 2x + 3 \) have the same y-value.
Let's look at the y-values from both equations in the table:
-
For \( x = 0 \):
- \( y = x + 6 = 0 + 6 = 6 \)
- \( y = 2x + 3 = 2(0) + 3 = 3 \)
-
For \( x = 1 \):
- \( y = x + 6 = 1 + 6 = 7 \)
- \( y = 2x + 3 = 2(1) + 3 = 5 \)
-
For \( x = 2 \):
- \( y = x + 6 = 2 + 6 = 8 \)
- \( y = 2x + 3 = 2(2) + 3 = 7 \)
-
For \( x = 3 \):
- \( y = x + 6 = 3 + 6 = 9 \)
- \( y = 2x + 3 = 2(3) + 3 = 9 \)
-
For \( x = 4 \):
- \( y = x + 6 = 4 + 6 = 10 \)
- \( y = 2x + 3 = 2(4) + 3 = 11 \)
The two equations yield the same y-value at \( x = 3 \), where both equations give \( y = 9 \).
Therefore, the solution to the system of equations is:
\[ (3, 9) \]